Stacking faults and the gamma-surface on first-order pyramidal planes in alpha-titanium - Ready,AJ; Haynes,PD; Rugg,D; Sutton,AP (Philosophical Magazine, 2017)
Using first principles methods we calculated the entire gamma-surface of the first-order pyramidal planes in alpha-titanium. Slip on these planes involving dislocations with c+a-type Burgers vectors is one means by which alpha-titanium polycrystals may supplement slip on prism planes with a-type Burgers vectors to maintain ductility. We find one low energy and one high energy stacking fault with energies of 163~mJ/m2 and 681~mJ/m2 respectively. Contrary to previous suggestions we do not find a stable stable stacking fault at (c+a})/2.